Origin of the Low Magnetic Moment in Fe₂AlTi: An Ab Initio Study - Friák, Martin; Slávik, Anton; Miháliková, Ivana; Holec, David; Všianská, Monika; Šob, Mojmír; Palm, Martin; Neugebauer, Jörg (Materials (Basel, Switzerland), 2018)
The intermetallic compound Fe 2 AlTi (alternatively Fe 2 TiAl) is an important phase in the ternary Fe-Al-Ti phase diagram. Previous theoretical studies showed a large discrepancy of approximately an order of magnitude between the ab initio computed magnetic moments and the experimentally measured ones. To unravel the source of this discrepancy, we analyze how various mechanisms present in realistic materials such as residual strain effects or deviations from stoichiometry affect magnetism. Since in spin-unconstrained calculations the system always evolves to the spin configuration which represents a local or global minimum in the total energy surface, finite temperature spin effects are not well described. We therefore turn the investigation around and use constrained spin calculations, fixing the global magnetic moment. This approach provides direct insight into local and global energy minima (reflecting metastable and stable spin phases) as well as the curvature of the energy surface, which correlates with the magnetic entropy and thus the magnetic configuration space accessible at finite temperatures. Based on this approach, we show that deviations from stoichiometry have a huge impact on the local magnetic moment and can explain the experimentally observed low magnetic moments.
Keywords: stability; strain; ab initio; Fe2TiAl; off-stoichiometry; Fe2AlTi; Heusler; magnetism